2017
DOI: 10.1002/2017wr020486
|View full text |Cite
|
Sign up to set email alerts
|

Role of organic phosphorus in sediment in a shallow eutrophic lake

Abstract: We tested the hypothesis that mineralization of molybdenum unreactive phosphorus (MUP) in pore water is the major pathway for the changes in the concentration of molybdenum‐reactive P (MRP) in pore water and inorganic P in sediment particles. The concentration of inorganic P in the sediment particles increased from December to April in Lake Kasumigaura, whereas concentrations of organic P in the sediment particles and MUP in pore water decreased. These results suggest that MUP mineralization plays a key role a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…An alternative explanation is that oxic conditions caused by the water level drawdown may have allowed adsorption of PO 4 3− onto the sediment solids, even if organic P had been mineralized. This explanation is consistent with the results of previous work, which have shown that mineralization of organic matter in the sediment plays a role in determining nutrient dynamics in the pore water where we collected the sediments in Lake Kasumigaura (Shinohara et al, 2017). However, the release of nutrients from sediments involves very complex processes that can result from a number of physical and biogeochemical mechanisms (Orihel et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…An alternative explanation is that oxic conditions caused by the water level drawdown may have allowed adsorption of PO 4 3− onto the sediment solids, even if organic P had been mineralized. This explanation is consistent with the results of previous work, which have shown that mineralization of organic matter in the sediment plays a role in determining nutrient dynamics in the pore water where we collected the sediments in Lake Kasumigaura (Shinohara et al, 2017). However, the release of nutrients from sediments involves very complex processes that can result from a number of physical and biogeochemical mechanisms (Orihel et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…It is also interesting to stress that as P I increased with reservoir age, P o decreased (Table 4). This trend is supported by the study of Shinohara et al (2017), in which the concentration of inorganic P in the sediment of a shallow eutrophic lake in Japan increased over time whereas the concentration of organic P decreased. Such a result suggests that organic P is converted into inorganic P, as bacteria in the sediment can decompose the organic matter, consuming oxygen and releasing inorganic P.…”
Section: Sediment Phosphorus Analysismentioning
confidence: 63%
“…where R G is the heat flux through the bottom sediment (W m À2 ), K sed is the thermal conductivity of sediment (¼0.25 W m À1 K À1 ), T w is the surface water temperature (K), T sed is the sediment temperature (K), and δz is the thickness of the sediment (m). Our observations involved monitoring water and sediment temperature monthly (Shinohara et al 2017). Based on the temperatures of the water and sediment at 0.0 m and 1.5 cm, we estimated the heat flux between the water and bottom sediment to be in the range of À4.0 to 8.0 W m À2 .…”
Section: Heat Fluxes Other Than Fluxes Through the Lake Surface: Uncertainties And Limitationsmentioning
confidence: 99%